Preliminary study on the coconut crab (Birgus latro) rearing in captive pond - . Sulistiono; M.M. Kamal; Nurlisa A. Butet (Jurnal Akuakultur Indonesia)
Preliminary study on the coconut crab (Birgus latro) rearing was employed in captive pond at Citarate village, Lebak Regency (Banten) from May to December 2008.  The rearing activity was done in captive pond sized 5x5x1.3 m3 divided into 22 smaller ponds sized 1x1x1.3 m3 with a hiding hole (constructed by pile stones), supported by two small ponds sized 30x40x40 cm3 for sea and fresh water stocks, respectively.  The coconut crab (N=22 individuals at cement pond I and N=18 individuals at cement pond II) were reared in each small ponds (density: 1 individual/pond), feed by a piece of coconut (20-50 gram per individual in each cement pond).  The coconut and the water (sea and fresh water) were replaced for 2-3 times per week. Result of the study showed that survival rate was around 82% (ponds I) and 83% (ponds II), and mortality was around 18% (ponds I) and 18% (ponds II). The coconut crab growth at captive ponds I and II were around 17.5 and 52 gram per month, respectively.